Effect of Doppler Shift frequency on the performance of 2x2 OSTBC-OFDM System - Diana Hayder Hussein; Thuraya Mahmood Qaradaghi (QALAAI ZANIST JOURNAL, 2021)
In this paper the effect of the Doppler shift frequency on the performance of the 2x2 MIMO system has been studied and presented. A system with two transmits antennas and two receive antennas has been used. Accurate and efficient channel estimation which plays a key role in MIMO-OFDM communication system has been implemented using pilots and training sequences. To guarantee a much more reliable and robust transmission over a hostile wireless channel, a convolutional codes have been added to the 2x2 MIMOOSTBC-OFDM system as a Forward Error Correction (FEC) codes. Two types of convolutional code rate have been used (1/2 and 2/3) depending on the type of modulation. To make this code more robustness against channel impairments; interleaving has been used with the convolutional code. The system has been evaluated for four types of QAM modulation (4-QAM, 8-QAM, 16-QAM, and 64-QAM) as a baseband modulation. The system has been evaluated for three different values of Doppler Shift frequency (5, 50, and 100) Hz. The simulation results demonstrated the performance of the systems over Flat and multi-path Frequency-Selective fading channels, assuming the channels are with No Line Of Sight (NLOS), so the channels are Rayleigh fading channels. The results show that when the Doppler Shift Frequency increased the BER also increases and when Doppler Shift Frequency is 5Hz, the performance of the system is better for four types of QAM modulation and in the two cases of Flat and multi-path Frequency-Selective fading.